Construction of Long‐Wavelength Emissive Organic Nanosonosensitizer Targeting Mitochondria for Precise and Efficient In Vivo Sonotherapy. (30th July 2022) - Zhang, Xiangqian; Li, Chonglu; Zhang, Yi; Guan, Xiaofang; Mei, Longcan; Feng, Huili; Li, Jie; Tu, Le; Feng, Guoqiang; Deng, Ganzhen; Sun, Yao
Abstract: As a modern biomedical therapeutic modality, sonodynamic therapy (SDT) presents unique advantages, including superior tissue penetration capability, temporal–spatial controllability, and negligible side effects. However, the bottlenecks of most organic sonosensitizers are their short emission wavelengths, strong phototoxicity, and unsatisfactory SDT effect, which undermines the precise fluorescence imaging‐guided SDT in vivo. Here, a long‐wavelength emissive and mitochondria‐targeted organic nanosonosensitizer, named CCNU980 nanoparticles (NPs), is rationally designed, which possesses deep‐tissue optical penetration (up to 6 mm), depth‐activated ROS production (up to 8 cm), high photostability, and low phototoxicity. In vitro studies verify CCNU980 NPs selectively enriches in cancer cells with the ability to target the mitochondria and induce mitochondria‐mediated apoptosis using abundant 1 O2 under US irradiation. Notably, CCNU980 NPs enables precise in vivo NIR‐II fluorescence imaging‐guided SDT, accompanied by the suppression of the bilateral 4T1 tumor growth with minimal side effects. The current work can inspire a general strategy for the design of organic nanosonosensitizers with long‐wavelength emission and new thoughts for precision medicine. Abstract : Herein, a long‐wavelength emissive and mitochondria‐targeted organic nanosonosensitizer is rationally designed, named CCNU980 nanoparticles, which enables the precise in vivo NIR‐II fluorescence imaging‐guided sonodynamic therapy, accompanied by the suppression of the bilateral 4T1 tumor growth with minimal side effects. The current work can inspire a general strategy for the design of organic nanosonosensitizers with long‐wavelength emission for precision medicine.